Construction and Application of Flocculation and Destability System of Biodrill-A Drilling Fluid in Bohai Oilfield - Ma, Yingwen; Zhang, Yuchen; Liu, Yang; Yue, Ming; Wang, Dongsen; Zhang, Xuemei (Frontiers in Energy Research, 2021)
To protect the marine ecological environment of Bohai Bay, the waste drilling fluid in Bohai oilfield have to be treated. In the light of the composition characteristics of Biodrill-A drilling fluid, the compounding method of the inorganic-organic flocculants was adopted to assist the flocculation and solid-fluid separation of Biodrill-A drilling fluid. Through the orthogonal test design, the main factors impacting the flocculation effect on Biodrill-A drilling fluid were found to the concentration of inorganic flocculant CaCl2 and the flocculation pH value. The optimal flocculation treatment was further obtained through single-factor optimization. Specifically, when the inorganic flocculant CaCl2 concentration was 0.9 w/v%, the organic flocculant concentration was 0.01 w/v%, the flocculation pH was 8, and the flocculation time was 7 min, eventually, the final dewatering rate could reach 84.02%. In the optimized compound flocculants, the inorganic flocculant CaCl2 reduced the zeta potential of clay particles by electric neutralization to decrease the repulsion among particles, and the organic one could absorb and wrap the clay particles through bridging curling and electric neutralization after flocculation destabilization. Both inorganic and organic flocculants facilitated the large flocs and particles of clay particles. The field test showed that the inorganic-organic flocculants were suitable for the on-line flocculation treatment process based on centrifugal machine. The waste drilling fluid was reduced by 82%, and the water content of the separated solid phase was as low as 25.7%.